Riina Turtio (2023) - State-Building and National Militaries in Postcolonial West Africa. Decolonizing the Means of Coercion (1958-1974) - Sarr, Pape (Revue d’histoire contemporaine de l’Afrique, 2023)
Recensé : Riina Turtio, State-Building and National Militaries in Postcolonial West Africa. Decolonizing the Means of Coercion (1958-1974), Rochester, James Currey, 2023, 360 p.